Decision‐making by the NICE Interventional Procedures Advisory Committee. Issue 13 (25th October 2019) - Carroll, C.; Dickson, R.; Boland, A.; Houten, R.; Walton, M.
Abstract : Background: This study explored the evidence base for recommendations by the National Institute of Health and Care Excellence (NICE) Interventional Procedures Advisory Committee, the only NICE committee not to consider cost. The four potential recommendations are: Standard Arrangements (can be performed as routine practice in the NHS); Special Arrangements (can be done under certain conditions); Research Only; and Do Not Do. Methods: Quantitative content analysis of data extracted from all published Interventional Procedure Guidance (IPG) for 2003–2018 ( n = 496) was undertaken. All data were extracted independently by two researchers; disagreements were clarified by consensus. Data were tabulated, descriptive statistics produced, and regression analyses performed. Results: The proportion of IPGs by recommendation was: 50·0 per cent Standard Arrangements; 37·2 per cent Special Arrangements; 11·1 per cent Research Only; and 1·6 per cent Do Not Do. There was a clear trend over time: the proportion of recommendations for Standard Arrangements decreased, whereas the evidence threshold increased. Adjusted mean numbers of patients in the evidence base by recommendation type were: Standard, 4867; Special, 709; Research Only, 386. Regression analyses confirmed that the year of recommendation, numbers of patients and levels of evidence all affected the likely recommendation. Conclusion: This study suggests that the likelihood of achieving the most positive recommendation (Standard Arrangements) is decreasing, and that this is most likely due to evidential requirements becoming more demanding. These findings are distinct from those reported for other NICE committees, for which the cost and statistical superiority of new therapies are among the drivers of recommendations. Abstract : The likelihood of a procedure receiving the most positive recommendation from the NICE Interventional Procedures Advisory Committee has decreased over time, while evidence requirements have increased. How NICE works Abstract : Antecedentes: Este estudio analiza los niveles de evidencia de las recomendaciones propuestas por el Interventional Procedures Advisory Committee del National Institute of Health and Care Excellence (NICE), el único comité NICE que no tiene en consideración los costes en la guía para los procedimientos de intervención. Las cuatro recomendaciones potenciales son: disposiciones estándar (se pueden efectuar sin restricciones en el marco del NHS); disposiciones especiales (se pueden efectuar bajo ciertas condiciones), en el ámbito de la investigación solo; y no intervenir. Métodos: Se realizó un análisis cuantitativo del contenido de todas las Interventional Procedure Guidance (IPG) publicadas entre 2003‐2018 ( n = 496). Se obtuvieron todos los datos de forma independiente por dos investigadores y los desacuerdos entre ellos se decidieron por consenso. Se tabularon los datos y se realizaron estadísticas descriptivas y análisis de regresión. Resultados: La proporción de las IPG según el tipo de recomendación eran estándar en el 50% de los casos, especial en el 37%, solo investigación en el 11% y no intervenir en el 2%. Se observó una clara tendencia a lo largo del tiempo: la proporción de recomendaciones del tipo de disposiciones estándar disminuía, mientras que el umbral para la evidencia aumentaba. La media ajustada del número de pacientes para cada tipo de recomendación (estándar, específica y solo investigación) fue de 4.867, 709 y 386, respectivamente. Los análisis de regresión confirmaron que el año de la recomendación, el número de pacientes y los niveles de evidencia afectaban el tipo de recomendación. Estos resultados son diferentes a los relativos a otros comités de NICE, en los que el coste y la superioridad estadística de las nuevas terapias son los motores de las recomendaciones. Conclusión: Este estudio sugiere que la probabilidad de lograr la recomendación más positiva (disposición estándar) está disminuyendo, y ello con toda probabilidad es debido a que los requerimientos relacionados con la evidencia son cada vez más exigentes.